Analysis of C-Reactive Protein as an Inflammation Indicator in Obese Adolescents - Ubaedillah, Muhammad Ibnu; Ibrahim Aji, Rizal; Ningsih, Trinina Rizkiya Salmiyah (Universitas An Nasher - Cirebon, 2025)
Obesity is excessive fat accumulation due to an imbalance between energy intake and energy expenditure, the prevalence of obesity in adolescents is increasing and causing metabolic syndrome. Production of C-Reactive protein (CRP) increases in adolescents with metabolic disorders and at risk of developing cardiovascular disease as adults. This study aims to determine C-Reactive Protein (CRP) in obese adolescents in Susukan Village, Susukan District, Cirebon Regency, and to determine the percentage of obesity that is positive on C-Reactive Protein (CRP) examination. In this study using descriptive methods and for examination using latex agglutination methods. Based on the results of a study of 36 people in Susukan Village, Susukan District, Cirebon Regency, as many as 32 people with a percentage (88.9%) got CRP negative results and 4 people with a percentage (11.1%) got CRP positive results. Based on this study it can be concluded that positive results were obtained on examination of C-reactive Protein (CRP) in obese adolescents in Susukan Village, Susukan District, Cirebon Regency